Triceps Surae Lengthening in Foot and Ankle Trauma: A Survey of OTA and AOFAS Members. Issue 3 (September 2022) - Patterson, Joseph T.; Campbell, Sean T.; Wallace, Stephen J.; Magnusson, Erik A.; Elliott, Iain S.; Mertz, Kevin; Benirschke, Stephen K.
Background: The prevalence, indications, and preferred methods for gastrocnemius recession and tendo-Achilles lengthening—grouped as triceps surae lengthening (TSL) procedures—in foot and ankle trauma are supported by a scarcity of clinical evidence. We hypothesize that injury, practice environment, and training heritage are significantly associated with probability of performing adjunctive TSL in the operative management of foot and ankle trauma. Methods: A survey was distributed to members of the American Orthopaedic Foot & Ankle Society and the Orthopaedic Trauma Association. Participants rated how likely they would be to perform TSL at initial management, definitive fixation, and after weightbearing in the presence and absence of a positive Silfverskiöld test in 10 clinical scenarios of closed foot and ankle trauma. Results: A total of 258 surgeons with median 14 years' experience responded. Eighty-five percent reported foot and ankle fellowship training, 24% reported traumatology fellowship training, 13% both, and 4% no fellowship. Ninety-nine percent reported performing TSL with a median 25 TSL procedures per year, 72% open gastrocnemius recession, and 17% percutaneous tendo-Achilles lengthening). Across all scenarios, we observed low overall 8% probability with fair agreement (κ = 0.246) of performing TSL (range, 1% at initial management of an unstable Weber B bimalleolar ankle fracture with negative contralateral Silfverskiöld test to 29% at definitive fixation of tongue-type calcaneus fracture with positive contralateral Silfverskiöld test). Silfverskiöld testing significantly influenced TSL probability at all time points. University of Washington training (β = 1.5, P = .007) but not trauma vs foot fellowship training, years in practice, academic practice, urban setting, or facility trauma designation were significantly associated with likelihood of performing TSL. Conclusion: Orthopaedic traumatology and foot and ankle surgeons report similar indications, methods, and low perceived propensity to use TSL in the management of foot and ankle trauma. We found that graduates of 1 fellowship training site were more likely to perform TSL in the setting of acute trauma potentially indicating the need for better scientific data to support this practice. Level of Evidence: Level V, therapeutic.